2006
DOI: 10.1016/j.micinf.2005.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between parasite cysteine proteases and the host kinin system modulates microvascular leakage and macrophage infection by promastigotes of the Leishmania donovani complex

Abstract: Kinins, the vasoactive peptides proteolytically liberated from kininogens, were recently recognized as signals alerting the innate immune system. Here we demonstrate that Leishmania donovani and Leishmania chagasi, two etiological agents of visceral leishmaniasis (VL), activate the kinin system. Intravital microscopy in the hamster cheek pouch showed that topically applied promastigotes induced macromolecular leakage (FITC-dextran) through postcapillary venules. Peaking at 15 min, the parasite-induced leakage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Our data demonstrated that L. amazonensis infection led to reduction of total p65 levels. Although we have not investigated the mechanisms involved in p65 cleavage, it is conceivable that L. amazonensis proteases [38][39][40][41][42][43] are mediators of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that L. amazonensis infection led to reduction of total p65 levels. Although we have not investigated the mechanisms involved in p65 cleavage, it is conceivable that L. amazonensis proteases [38][39][40][41][42][43] are mediators of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the HCP with HOE-140 or L -NA prior to maxadilan resulted in no visible changes, suggesting that kinin formation does not play an important role in the microvascular effects induced by maxadilan (data not shown). Given indications that L. chagasi promastigotes can induce edema and infect macrophages through the activation of the kinin pathway [34], it will be interesting to determine if the convergence of these responses may have short- or long-lasting effects on the host-parasite relationship. This hypothesis merits analysis in light of recent studies showing that bradykinin, recently characterized as a potent maturation signal for dendritic cells, links innate to type-1 adaptive immunity in mice infected with Trypanosoma cruzi [51] (for a review, see Scharfstein et al [52]).…”
Section: Discussionmentioning
confidence: 99%
“…A tracheal cannula (PE 190) was inserted to facilitate spontaneous breathing, and the body temperature was maintained at 37°C using a heating pad connected to a rectal thermistor probe. HCP was prepared and used for intravital microscopy as previously reported [32,33,34]. Briefly, the cheek pouch was everted and mounted on a microscope stage, and an area of about 1 cm 2 was prepared for intravital microscopy observations of the microcirculation.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…Furthermore, it was proposed that L. donovani and L. chagasi cysteine peptidases activate the kinin system, a group of potent vasoactive peptides proteolytically liberated from kininogens, which have been recognized as signals alerting the innate immune system [141].…”
Section: Cysteine Peptidasesmentioning
confidence: 99%